Microscopic Agglutination Test for Diagnosis of Leptospirosis by Using Filter Paper-Dried Serum Samples - Yogita Mistry; Tanvi Panwala; Summaiya Mullan (Medical Laboratory Journal, 2021)
Background and objectives: Microscopic agglutination test is the gold standard sero-diagnostic method for detection of leptospirosis. Moreover, it helps identify serovars and their titers in serum samples. For obtaining accurate titer results, proper sampling, collection, storage, and transportation of samples are crucial while maintaining the cold chain. Since storage for long periods and the subsequent deterioration of samples may affect the final titers, we proposed an alternative method of MAT testing using filter paper-dried serum samples. We also evaluated sensitivity and specificity of the MAT test by using filtered-dried serum samples compared with the conventional MAT test. Methods: This experimental study was performed on human and animal serum samples that were sent to a reference leprospirosis laboratory in 2020. Overall, 142 positive samples (with 289 titers for different strains) and 15 negative samples were used for MAT test using filtered-dried serum. For this purpose, each sample was dried on a filter paper (Whatman 903, GE Healthcare) at room temperature (20-30 °C) and kept for four days. On the fifth day, the filter papers were cut into small pieces, soaked in phosphate buffer saline, vortexed, and slowly mixed on shaker for two hours to elute antibodies. The MAT tests were performed simultaneously and under the same environmental conditions. Results: The new MAT test using dried serum samples showed 79% sensitivity and 100% specificity. The test also had positive predictive value of 92% and negative predictive value of 24% when compared with the gold standard MAT test. Conclusion: Filter-dried serum can be used for MAT test to overcome serum storage and transportation problems.